Efek Nefroprotektor Ekstrak Biji Mahoni (Swietenia mahagoni (L.) Jacq.) terhadap Kerusakan Histologis Sel Ginjal Mencit (Mus musculus) yang Diinduksi Parasetamol - Muvida Muvida; . Muthmainah; Yulia Sari (Nexus Biomedika, 2013)
Background: Seed extract of Swietenia mahagoni (L.) Jacq. contains saponins, flavonoids, alkaloids, terpenoids, steroids, and tannins that may exhibit significant protection of kidney cells from free radicals. In present study, Swietenia mahagoni was evaluated for its nephroprotector effect on paracetamol-induced kidney cells histological damage in mice (Mus musculus). Methods: This research used experimental laboratory studies with post test only controlled group design. Samples were 28 male Swiss webster mice (2-3 months old) weighing + 20 g and divided into 4 groups, 7 mice each group. Sampling technique in this research was incidental sampling. The negative control group (KK (-)) and the positive control group (KK (+)) of mice were administered aquadest for 14 days. The first treatment group (KP1) and the second group treatment (KP2) of mice were administered mahagony seed extract with the dose of 11,2 mg/20 g and 22,4 mg/20 g body weight of mice for 14 days, respectively. Paracetamol was administered to groups of KK (+), KP1, dan KP2 on the 12th, 13th, and 14th day. On day-15th, mice were sacrificed and their kidneys were taken and stained with hematoxilin eosin (HE) for histological study. The kidney cells histological features were assessed based on quantifying of pyknosis, karyorrhexis, and karyolysis. Data were analyzed with the One-Way ANOVA test (? = 0.05) and Post Hoc Multiple Comparisons LSD test (? = 0.05). Results: The mean of kidney cells histological damage in mice for KK (-), KK (+), KP1 and KP2 were 9.57 + 0.701; 28.93 + 1.698; 9.28 + 0.873 and 27.79 + 1.651, respectively. Result of statistic analysis showed that there were significant differences of kidney cells damage score between KK (-) KK (+), KK (-) KP2, KK (+) KP1, KP1 KP2, and non significant differences between KK (-) KP1 and KK (+) KP2. Conclusions: Swietenia mahagoni (L.) Jacq. seed extract showed nephroprotector effect against paracetamol-induced kidney cells histological damage in mice. Keywords: mahagony seed extract, nephroprotector, kidney cells histological damage